Spatial channel network (SCN): Opportunities and challenges of introducing spatial bypass toward the massive SDM era [invited] - Jinno, Masahiko (Journal of optical communications and networking, 2019)
Considering middle-term predictions of the need for commercial 10-Tb/s optical interfaces working in 1-P b/s optical transport systems by 2024 and recalling the introduction of the optical bypass when entering the wavelength-abundant era in the early 2000s, we re-evaluate the values of hierarchical optical network architecture in light of the forthcoming massive spatial division multiplexing (SDM) era. We introduce a spatial channel (SCh) network (SCN) architecture, where the SDM layer is explicitly defined as a new networking layer that supports the new multiplexing technology of SDM. In an SCN, optical channels (OChs) accommodated in an express SCh bypass the overlying wavelength cross-connects (WXCs) using spatial cross-connects (SXCs) on the route. As one challenge that SCNs will present, we point out that an excessively large SXC insertion loss reduces the optical reach for spectrally groomed OChs. We show that the optical reach of spectrally groomed OChs can be maintained at almost the same level as that for an OCh transported through a conventional single-layer WDM network thanks to the low-loss features of commercially available spatial switches and foreseeable low-loss SDM multiplexers and demultiplexers. As another challenge, we discuss how to achieve growable, reliable, and cost-effective SXCs. We propose two SXC architectures based on sub-matrix switches and core-selective switches. Simple cost assessment shows that the proposed architectures are more cost-effective than the full-size matrix switch-based architecture with 1 + 1 equipment protection and conventional stacked WXC architecture.